Implementation and Outcomes of a Telehealth Neonatology Program in a Single Healthcare System - Maddox, Lory J.; Albritton, Jordan; Morse, Janice; Latendresse, Gwen; Meek, Paula; Minton, Stephen (Frontiers in Pediatrics, 2021)
Background: Intermountain Healthcare, an early adopter and champion for newborn video-assisted resuscitation (VAR), identified a reduction in facility-level transfers and an estimated savings of 1.2 million in potentially avoided transfers in a 2018 study. The current study was conducted to increase understanding of VAR at the individual, newborn level. Study aim: To compare transfer, length of stay (LOS), and days of life on oxygen between newborns managed by neonatal VAR and those receiving standard care (SC). Methods: This retrospective, nonequivalent group study includes infants born in an Intermountain hospital between 2013 and 2017, 34 weeks gestation requiring respiratory support in the first 15 minutes of life. Data came from billing and clinical records from Intermountain's enterprise data warehouse and chart reviews. We used logistic regression to estimate neonatal VAR's impact on transfers. Negative binomial regression estimated the impact on length of stay and days of life on supplemental oxygen. Results: The VAR intervention was used in 42.6 percent of cases and is associated with 1) a 12 percentage points reduction in the transfer rate, p = .02, 2) a reduction in spoke hospital (SH) LOS of 8.33 hours ( p < .01) for all transfers; 3) a reduction in SH LOS of 2.21 hours (p < .01) for newborns transferred within 24 hours; 4) a reduction in SH LOS of 17.85 hours (p = .06) among non-transferred newborns; 5) a reduction in days of life on supplemental oxygen of 1.4 days (p = .08) among all transferred newborns, and 6) a reduction in days of life on supplemental oxygen of 0.41 days (p = .04) among non-transferred newborns. Conclusion: This study provides evidence that neonatal VAR improves care quality and increases local hospitals' capabilities to keep patients close to home. There is an ongoing demand for support to rural and community hospitals for urgent newborn resuscitations and complex, mandatory NICU transfers. Efforts may be necessary to encourage neonatal VAR since the intervention was only used in 46.2 percent of this study's potential cases. Additional work is needed to understand the short- and long-term impacts of Neonatal VAR on health outcomes.